Geopolitical Interstices: Social Risk Determinants - Saucedo-Arteaga, Gabriel Justo (Journal of Applied Business and Economics, 2021)
The interstice is a space where three or more states, or municipalities, converge, with low: accessibility, development and natural resources; social conflicts and instability. Interstices with conflicts can be identified: bordering, agrarian, socio-environmental; armed groups, drug trafficking and in indigenous regions, among others. This concept has been constructed based on macro ethnographic studies (participant observation) in regions of the Estado de Mexico and la sierra Tarahumara; previous investigations and news of local conflicts. It uses the official cartography, about: social backwardness, poverty, marginalization, indigenous population, human development and criminality. The interstices have economic and geographical conditions, but the political will and responsibility is unavoidable. They seem to be "no man's land" or empty spaces of power, because they do not represent an economic or political interest for the State; on the contrary, they do facilitate the development of capital and factual power groups that evade corrupt laws or regulations and put the population at risk.